Influence of Curing Age and Mix Composition on Compressive Strength of Volcanic Ash Blended Cement Laterized Concrete - Olawuyi, B.J.; Olusola, K.O.; Babafemi, A.J. (Institute of Research and Community Outreach - Petra Christian University, 2012)
This study investigates the influence of curing age and mix proportions on the compressive strength of volcanic ash (VA) blended cement laterized concrete. A total of 288 cubes of 100mm dimensions were cast and cured in water for 3, 7, 28, 56, 90 and 120 days of hydration with cement replacement by VA and sand replacement by laterite both ranging from 0 to 30% respectively while a control mix of 28-day target strength of 25N/mm2 (using British Method) was adopted. The results show that the compressive strength of the VA-blended cement laterized concrete increased with the increase in curing age but decreased as the VA and laterite (LAT) contents increased. The optimum replacement level was 20%LAT/20%VA. At this level the compressive strength increased with curing age at a decreasing rate beyond 28 days. The target compressive strength of 25N/mm2 was achieved for this mixture at 90 days of curing. VA content and curing age was noted to have significant effect (α ≤ 0.5) on the compressive strength of the VA-blended cement laterized concrete.